2003
DOI: 10.1111/1540-5907.00018
|View full text |Cite
|
Sign up to set email alerts
|

The Media, the Campaign, and the Message

Abstract: This article examines the 1996 press releases issued by Republican presidential nominee candidates during the invisible primary and the subsequent stories generated by these press releases in newspapers. We systematically examine how campaigns structure their messages, which messages are transmitted by the press to the voting public, and what factors influence the transmission of the campaign's message. We find that campaign organizations disseminate a variety of messages to the media. Our analysis demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…With the onset of the primary elections, however, media slid into horse-race mode: election coverage concentrating on who is ahead in the race for votes and money while largely ignoring issues and policies (Flowers et al, 2003), which Lawrence (2010) calls the 'game frame'. Eventually, the media grew overwhelmingly reliant on the Election Impact Frame, relegating the frame contest to background noise.…”
Section: Framing the Tea Party Movementmentioning
confidence: 99%
“…With the onset of the primary elections, however, media slid into horse-race mode: election coverage concentrating on who is ahead in the race for votes and money while largely ignoring issues and policies (Flowers et al, 2003), which Lawrence (2010) calls the 'game frame'. Eventually, the media grew overwhelmingly reliant on the Election Impact Frame, relegating the frame contest to background noise.…”
Section: Framing the Tea Party Movementmentioning
confidence: 99%
“…To examine other factors that may affect how newspeople name the candidates, we also provide the following ancillary hypotheses. First, previous literature has shown that a candidate's coverage is partially dependent on his or her electability and standing in polls (Flowers, Haynes, and Crespin 2003;Ridout 1993;John 1989). Candidates who poll well garner better coverage than candidates who poll poorly and have little chance of winning.…”
Section: Hypothesesmentioning
confidence: 99%
“…While the political psychology literature makes clear the powerful role that emotional appeals can play on a variety of forms of mass political behavior and public opinion, scholars of campaign communication have been slow to fully appreciate their influence. Instead, attention has more often gone to the candidates' issue agendas (Conway et al, 2015;Conway-Silva et al, 2018;Flowers et al, 2003;Hayes, 2010;Hayes & Lawless, 2016;Scott, 2021aScott, , 2021bVavreck, 2009), tone (Payne & Baukus, 1988;West, 2010), traits (Seifert, 2012), appeals to American values (Hart, 2000), and attacks on rivals (Benoit, 2007;Benoit & Rill, 2012). While these subjects are undoubtedly important, the content of candidates' emotional agendas has been relatively underevaluated (but see Borah, 2016;Brader, 2006;Jerit, 2004;Ridout & Searles, 2011).…”
Section: The Role Of Emotions In Campaignsmentioning
confidence: 99%